2000
DOI: 10.1034/j.1399-0012.2000.140504.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial venous thrombosis of the pancreatic allografts after simultaneous pancreas–kidney transplantation

Abstract: Despite new advances in transplantation, complete venous thrombosis (VT) of the pancreas after simultaneous pancreas kidney (SPK) transplantation usually results in graft loss. Data are limited regarding the outcome and treatment of partial VT of the pancreas allograft. From July 1994 to December 1999, 126 patients with IDDM/end-stage renal disease underwent SPK with systemic bladder drainage at the University of Miami. We retrospectively reviewed our experience regarding the outcome and treatment options of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…reported 6 patients with partial PAT of the splenic vein, who were started on aspirin 81 mg once daily and followed with serial Doppler USS. None progressed to complete thrombosis, and all had a functioning graft at the end of follow‐up 31. Delis et al.…”
Section: Discussionmentioning
confidence: 95%
“…reported 6 patients with partial PAT of the splenic vein, who were started on aspirin 81 mg once daily and followed with serial Doppler USS. None progressed to complete thrombosis, and all had a functioning graft at the end of follow‐up 31. Delis et al.…”
Section: Discussionmentioning
confidence: 95%
“…The pancreas graft is uniquely susceptible to vascular thrombosis due to its intrinsically low blood flow, which can be further diminished by ischemiaereperfusion injury [10].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment choice depends on thrombosis location and extension, operator experience, and availability of skilled interventional radiologists [3]. Kuo et al [6] and Ciancio et al [7] reported that venous thrombosis after pancreas transplantation could be treated with heparin and subsequent oral anticoagulation or aspirin depending on the thrombus extension. However, in the study of Kuo et al [6], the results of anticoagulation treatment were significantly worse in the recipients of solitary pancreas transplantation (26.8 %) compared with the recipients of simultaneous kidney and pancreas transplantation (86.1 %) despite the fact that venous graft thrombosis was diagnosed earlier in patients with solitary pancreas transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of randomization and a control group treated with anticoagulation prevents to assess in what number of these patients, particularly those with thrombus 30-60 % in length, anticoagulation alone would have been effective. The current literature dealing with the available salvage strategies is retrospective without comparing the different treatment options [4][5][6][7][8][9][10][11][12]. The low incidence of PVGT makes it difficult to compare the treatment options in a prospective randomized study in a single institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation